Environmental Awareness as a Predictor of English Teachers’ Professional Identity: A Correlational Study - Friscilla Sembiring (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Environmental awareness has become increasingly relevant to teachers’ professional roles because education is expected to contribute not only to academic achievement but also to sustainability-oriented values, responsible citizenship, and meaningful social transformation. For English teachers, environmental awareness may influence how they interpret their role as educators, integrate global issues into language learning, and develop a stronger sense of professional responsibility. This study investigated the relationship between environmental awareness and English teachers’ professional identity. The study employed a quantitative correlational design involving 40 English teachers. Two instruments were used: a 20-item Environmental Awareness Scale and a 20-item Professional Identity Scale. Both instruments used a five-point Likert scale, with total scores ranging from 20 to 100. The data were analyzed using descriptive statistics, level categorization, Pearson product-moment correlation, and simple linear regression. The findings showed that English teachers had a high level of environmental awareness, with a mean score of 82.60 and a standard deviation of 6.36. Their professional identity was also high, with a mean score of 84.93 and a standard deviation of 6.09. The correlation analysis revealed a very strong, positive, and statistically significant relationship between environmental awareness and professional identity, r = .997, p < .001. The regression analysis showed that environmental awareness significantly predicted professional identity, R² = .995, F (1, 38) = 7198.14, p < .001. The regression equation indicated that every one-point increase in environmental awareness was associated with a .96-point increase in professional identity. The study concludes that English teachers who demonstrate stronger environmental awareness tend to report stronger professional identity. These findings suggest that sustainability-oriented awareness may become an important dimension in strengthening English teachers’ professional meaning, responsibility, reflective practice, and instructional commitment.